The Relationship Between Self-Concept And Emotional Intelligence In Early Adulthood - Khoiriyah, Atta Nasyitul; Widyana, Rahma; Aziza, Maghfira Nur; Sesotya , Ratna (Indonesian Scientific Publication, 2024)
This study aims to determine the relationship between self-concept and emotional intelligence in early adulthood. The hypothesis in this study is that there is a significant positive relationship between self-concept and emotional intelligence in early adulthood. The subjects in this study were early adults aged 18-25 years. The research method used was a quantitative approach with a correlational design. Data collection was conducted using an emotional intelligence scale and a modified self-concept scale from previous research. The sampling technique employed purposive sampling to ensure the selected individuals met the criteria of early adulthood. The data analysis method used product moment correlation analysis (Pearson correlation). The results of the analysis obtained (r_xy) = 0.854 with a significance of 0.000 (p < 0.05). This shows that there is a significant positive relationship between self-concept and emotional intelligence in early adulthood. The coefficient of determination (R^2) is 0.729. This means that self-concept effectively affects emotional intelligence by 72.9%, and the remaining 27.1% is influenced by other factors not examined in this study.